T Cell Epitope Prediction and Its Application to Immunotherapy - Schaap-Johansen, Anna-Lisa; Vujović, Milena; Borch, Annie; Hadrup, Sine Reker; Marcatili, Paolo (Frontiers in Immunology, 2021)
T cells play a crucial role in controlling and driving the immune response with their ability to discriminate peptides derived from healthy as well as pathogenic proteins. In this review, we focus on the currently available computational tools for epitope prediction, with a particular focus on tools aimed at identifying neoepitopes, i.e. cancer-specific peptides and their potential for use in immunotherapy for cancer treatment. This review will cover how these tools work, what kind of data they use, as well as pros and cons in their respective applications.